Social Network Analysis (SNA) : a study of a Social Network in the forum Proedi - Lisbôa, Eliana Santana (2012)
The study that we present in this article deals with the analysis of the interactions of the social network forum PROEDI, titled Educational Podcasting. The Social network analysis (SNA), through matrix data, allows you to create a list of nodes (node - every element of the network elements) and connections (established relations between the nodes), and create a graph of links which, in our case, we call "interactions". By analyzing the graphic and the various indicators (centrality, density, intermediation and closeness) we understand the position of the members of the network, identify whether the group is cohesive or not and also identify which members have greater influence in the group. The results obtained in the analysis of this forum show that the network has a density level that reveals a large involvement and engagement in the discussion group, thus allowing a flow of information fairly equal among the members. However, and although the data obtained indicate the great commitment of the group to interact, there are elements that assume control of communication, whether in sending or receiving the information. This is a new data, because in previous studies, conducted by researchers in the social network PROEDI, this role was taken over entirely by the e-moderator of the network, which did not happen in this case and that can be justified, in the perspective of the authors, by thematic debate that somehow stimulated and urged members to participate more actively and committed.